Effects of Segmentation as a Word Recognition Strategy on the Reading Performance of Pupils with Reading Difficulties in Two Primary Schools in Tubah-Sub Division, North West Region of Cameroon - Nabi, Yigha Comfort (Journal of Innovation in Education and Social Research, 2024)
The study set out to investigate if segmentation as a word recognition strategy has an effect on the reading performance of learners with reading difficulties. The motivation for the study arose from the researcher’s observation that pupils leave primary schools and go to secondary schools when they can neither read nor spell simple words, and they even find it difficult to sound the letters of the alphabet. A sample of 50 pupils was purposely selected from two primary schools (a government and a private school) and data were collected with the use of four instruments: a reading readiness assessment test, an oral reading test for pupils with reading difficulties, an observation check list and teacher’s records of pupils’ performance. The study adopted a true experimental research design. The type of true experimental design used in the study was the pre-test post-test only control design with random assignment. Data were analyzed using the Statistical Package for Social Sciences (SPSS) version 20. Descriptive statistics was used to describe the basic features of the data in the study. Frequency tables were used containing frequencies, percentages and cumulative percentages of the various weighted responses in the experimental study as well as bar charts for clear visual representation of the frequencies and percentages of the observed phenomena. The findings revealed that segmentation as a word recognition strategy, increases pupils’ reading proficiency (from 8.0% in the control group to 68.0% in the experimental group.